2020
DOI: 10.3389/fimmu.2019.02976
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Induced Changes in the Immune Response in Pregnant Mice

Abstract: Faas et al.Microbiome, Immune Response, Pregnancy pregnancy in mice. The different immunological adaptations to pregnancy between conventional and germfree mice, such as the increase in Treg and tendency to an increase in Th2 cells in conventional pregnant mice only, may suggest that the microbiota may play a role in adapting the maternal immune response to pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…The expression of CD16 and CD14 allows the identification of three types of monocytes, i.e., classical, intermediate, and nonclassical. These cells are modified during pregnancy: the subpopulation of intermediate monocytes increases, while classical monocytes decrease and there are no changes in the nonclassical subpopulation 23 . Here, we show that all monocyte populations were not phenotypically different between infected or noninfected women, indicating that likely these cells do not participate in the creation of an inflammatory milieu.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CD16 and CD14 allows the identification of three types of monocytes, i.e., classical, intermediate, and nonclassical. These cells are modified during pregnancy: the subpopulation of intermediate monocytes increases, while classical monocytes decrease and there are no changes in the nonclassical subpopulation 23 . Here, we show that all monocyte populations were not phenotypically different between infected or noninfected women, indicating that likely these cells do not participate in the creation of an inflammatory milieu.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we investigated whether the effects of supplemented feeds on NK cells and microbiota were related. Although similar analysis of correlation between immune cells and specific microbial taxa has been performed in mice [84], it has not been conducted in chickens. Both supplemented feeds enhanced CD107 expression on intraepithelial NK cells and increased relative abundance of commensal LAB at 7 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies reported that expression of some immune genes in placenta could be unexpected because of variable reasons, such as epigenetic modification and its unique microenvironment [ 18 , 19 ]. In addition, pregnant mice raised in conventional and germ-free environment represented different immunological adaptations [ 20 ]. These studies suggested that un identified immune modulation were occurred during pregnancy.…”
Section: Discussionmentioning
confidence: 99%